Leader’s strategies for designing the promotional path of regional brand competitiveness in the context of economic globalization - Li, Pei; Du, Jianguo; Shahzad, Fakhar (Frontiers in Psychology, 2022)
In the era of economic globalization, the competitiveness of products on a global scale is increasingly achieved through effective and sustainable strategies for brand development by the leaders. This paper conducts an empirical study on regional brand competitiveness (BC) influencing factors. A research model was proposed and tested by employing structural equation modeling. Data analysis was conducted using 214 valid questionnaires from two major producing areas in Jilin Province, China. Research results show that Brand Market (BM) and Government Guidance (GG) directly and positively impact the regional BC. Regional Resource (RR) and industrial development (ID) indirectly impact the regional BC through the mediating role of BM and GG. BM is the most important factor affecting the regional BC. Based on this, the path to improve the competitiveness of traditional agricultural products under economic globalization is determined, and targeted countermeasures and suggestions are formulated for the existing problems.